Obesidade, sobrepeso, e doenças correlacionadas entre profissionais de uma unidade hospitalar - Ferreira, Paulo Henrique Panelli (2018)
Objective: To evaluate the association between work activities, sociodemographic characteristics, life habits and health history with the profile of overweight and obesity of the health professionals of a hospital unit. Materials and Methods: A cross-sectional study, performed in a general hospital, in the closed (intensive care, emergency, surgical center) and open (other sectors) sectors, with 308 workers with different functions. A questionnaire addressing sociodemographic and labor characteristics was applied as well as anthropometric measurements were verified. Bivariate and descriptive analyzes were performed applying the chi-square test. Results: Waist circumference was inadequate in 32.5% of the workers. Regarding body mass index, 57.4% of the workers had inadequate classification, 16.4% with obesity. There was a significant association between overweight and age, increased waist circumference (WC), male sex, low schooling, offspring, sedentary lifestyle, smoking history, use of antihypertensive drugs, work in open areas and a number of worked hours up to 40 per week. It was identified a significant association between obesity and age, increased WC, female, offspring, sedentary lifestyle, smoking history, use of antihypertensive drugs and hypercholesterolemia, family history of early coronary disease, administrative and nursing work, work in open sectors and a number of worked hours up to 40 per week. Conclusion: There was a high percentage of overweight in the hospital workers investigated. The advancement of obesity in our society requires efforts aimed at prevention and control of diseases related to overweight. The inclusion of healthy eating habits and the stimulation of physical exercise are interventions that can be implemented in the work environment; and may act as facilitators of overweight control in this population.